Serum ADAM17 levels pre-antiviral therapy correlate with HIV patient immune reconstitution - Ying Lin; Ming Chen; Xuelian Zhu; xiaoya cui; Suyu Sun; Xingzhong Hu (Heliyon)
Background: The relationship between tumour necrosis factor (TNF) levels and disease progression is well-established. However, the impact of changes in the level of TNF hydrolase (A-disintegrin and metalloenzyme 17; ADAM17) in HIV patients remains to be fully elucidated. Methods: Between March 1 and December 31, 2017, data were collected from 64 HIV-positive individuals in Wenzhou. Based on their history of antiviral treatment at the time of enrollment, these patients were categorized into two cohorts: an antiviral-treated group and an untreated HIV group. Then, the serum ADAM17 levels of each group were measured and analysed. Results: In comparison to the antiviral-treated group and the control group, the untreated HIV group exhibited a significantly elevated serum ADAM17 level (p < 0.001). A significant negative correlation was observed between serum ADAM17 levels and CD4+ T cell counts in the untreated HIV group (r = −0.486, p = 0.001). ROC curve analysis revealed that the pre-treatment serum ADAM17 level in the untreated HIV group had moderate diagnostic accuracy for the AIDS stage (area under the curve: 0.703, p = 0.028). Additionally, serum ADAM17 levels were positively correlated with ADAM17 expression on the surface of leukocytes (r = 0.367, p = 0.018). Conclusion: Serum ADAM17 levels are significantly elevated in HIV patients and are correlated with disease progression and immune reconstitution.